Medial Temporal Lobe Atrophy and Depressive Symptoms in Elderly Patients With and Without Alzheimer Disease. (March 2015) - Enache, Daniela; Cavallin, Lena; Lindberg, Olof; Farahmand, Bahman; Kramberger, Milica Gregoric; Westman, Eric; Jelic, Vesna; Eriksdotter, Maria; Ballard, Clive; Winblad, Bengt; Wahlund, Lars-Olof; Aarsland, Dag
Objective: To determine whether depressive symptoms are associated with medial temporal lobe atrophy in older people with and without Alzheimer disease (AD). Method: A total of 368 memory clinic patients with AD, mild cognitive impairment, and subjective cognitive impairment (SCI) were included. Depressive symptoms were defined as a score of 8 or higher on Cornell Scale for Depression in Dementia or use of antidepressant medications. Magnetic resonance imaging and computer tomography scans were rated for medial temporal lobe atrophy (MTA), using the Scheltens scale. For a subsample (n = 57 patients), hippocampal volume was manually traced. Results: Based on visual assessment, AD patients with depressive symptoms had less atrophy of the right medial temporal lobe (odds ratio [OR] for having MTA: 0.39; 95% confidence interval [CI] 0.16-0.99) and decreased scores on Scheltens scale for the left medial temporal lobe (OR: 0.43, 95% CI 0.19-0.96) in comparison to AD patients without depressive symptoms. In the subgroup where manual tracing was used to measure hippocampal volume, people with SCI experiencing depressive symptoms had smaller right (mean difference: 0.28 cm 3 ; P = .005) and left (mean difference 0.32 cm 3 ; P = .002) hippocampal volumes compared to people with SCI who did not have depressive symptoms. Conclusion: Hippocampal atrophy was more pronounced among patients having SCI with depressive symptoms, while the medial temporal lobe was less atrophic in patients having AD with depressive symptoms than those without depressive symptoms. These findings suggest that different mechanisms underlie depression in older people with and without AD and may explain some of the inconsistent observations in previous studies.